Broadband Duct Noise Reduction Using Multi-chamber Micro-perforated Panel Absorbers - Bennett, Gareth (American Institute of Aeronautics and Astronautics, 2024)
This study explores the efficacy of Multi-chamber Micro-perforated Panel Absorbers (MC- MPPAs), a newly identified metamaterial, as a liner for attenuating noise within duct walls. The project aimed to develop MC-MPPA liners implemented across all four walls of the duct, engineered to attenuate noise over a broad frequency range from 500Hz to 4500Hz. Each of the four liners, with a depth of only 35 mm, was optimized for different, overlapping frequency ranges to maximize duct noise reduction. Experimental results demonstrated a significant noise transmission reduction, with MC-MPPA liners achieving an insertion loss of 15-20 dB on average, and a peak reduction of 40 dB at around 1500 Hz, compared to a hard-wall baseline. This substantial reduction in Sound Pressure Level (SPL) not only proves the potential of MC-MPPA as an effective sound attenuation material but also highlights its applicability in enhancing duct noise control technologies. The success of this project offers a promising solution in duct noise reduction strategies
30th AIAA/CEAS Aeroacoustics Conference
30th AIAA/CEAS Aeroacoustics Conference